KNOWLEDGE AND PERCEPTION OF STUDENTS ABOUT PEAT: ITS IMPLEMENTATION IN LEARNING SCIENCE IN JUNIOR HIGH SCHOOL - Bambang Hariyadi; Agus Subagyo; Adinda Mutiara Ulfa (Universitas Negeri Surabaya in collaboration with Perkumpulan Pendidik IPA Indonesia (PPII), 2023)
Natural peatlands are home to a wide variety of animals and plants and provide ecosystem services for humans and the environment. Peatlands in Jambi are still not appropriately managed, partly because of the lack of community knowledge regarding peat. This study reveals the knowledge and perceptions of junior high school students about peat, the factors that influence it, and its implementation in science learning. We conducted the study on 228 junior high school students and 21 science teachers in Tanjung Jabung Timur. Data were collected through questionnaires, observations, and focused discussions. Data were analyzed descriptively. Furthermore, the data were analyzed using Smart PLS to determine the relationship between students' background, perceptions, and interactions with their knowledge of peat. Students' knowledge of peat is in a low category. The level of student's knowledge is significantly influenced by their experiences (interactions) with peatlands and their perceptions of these resources. The student's family background does not affect students' knowledge of peat.